2018
DOI: 10.3390/en11040777
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation Processes and Skills Supporting EcoCity Development

Abstract: Ecocities can provide solutions for the improvement of human settlements around the world and the living conditions therein, but in the authors' experience, only as long as they are able to address the following questions correctly: How to formulate an ecocity concept that, considering issues of general concern, can be at the same time adapted to different local conditions? What are the instruments supporting the development and implementation of ecocity solutions? VTT's EcoCity concept for sustainable communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Experience from a number of EcoCity projects and activities worldwide corroborates the importance of adaptation to the local context due to varying socio-economic, socio-political, socio-ecological and cultural conditions as explained by Antuña-Rozado et al [8] and illustrated through EcoMedellín and EcoLusaka case studies [8]. Supporting communities to develop and implement their own definition of sustainability is essential to the purpose, very much in line with Roseland [9] for whom there is not one universal definition of the ecocity and perhaps there should not be.…”
Section: Local Definition (Negotiated and Agreed) Of Sustainabilitymentioning
confidence: 64%
See 4 more Smart Citations
“…Experience from a number of EcoCity projects and activities worldwide corroborates the importance of adaptation to the local context due to varying socio-economic, socio-political, socio-ecological and cultural conditions as explained by Antuña-Rozado et al [8] and illustrated through EcoMedellín and EcoLusaka case studies [8]. Supporting communities to develop and implement their own definition of sustainability is essential to the purpose, very much in line with Roseland [9] for whom there is not one universal definition of the ecocity and perhaps there should not be.…”
Section: Local Definition (Negotiated and Agreed) Of Sustainabilitymentioning
confidence: 64%
“…The aim of the research shown here is two-folded. On the one hand, to frame the theoretical and historical underpinnings of the concept in relation to the general ecocity debate, thus completing the trilogy including the two previous articles [8,18] focusing on its practical side and covering the methodologies and facilitation processes and skills specifically developed to support the implementation of the concept. On the other hand, to exemplify through a case study how the concept is applied in practice in a specific local context…”
Section: Research Aim Methodology and Novelty Of The Approachmentioning
confidence: 99%
See 3 more Smart Citations